2022
DOI: 10.1002/aenm.202201323
|View full text |Cite
|
Sign up to set email alerts
|

Restraining the Octahedron Collapse in Lithium and Manganese Rich NCM Cathode toward Suppressing Structure Transformation

Abstract: Compared with the advanced anode, the energy density of LIBs is more largely determined by discharge capacity and voltage of the cathode. [3][4][5] Lithium and manganese rich nickel cobalt manganese oxide (LMRNCM), xLi 2 MnO 3 •(1-x)LiTMO 2 (TM (transition metal) = Mn, Ni, Co), has been considered as an attractive next-generation cathode candidate owing to its high energy density (≈1000 Wh kg −1 ) and low cost. [6] According to the charge compensation mechanism and the energy level theory, when the Li + extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…105,106 Cation doping and interface engineering are two of the efficient strategies to prevent the lattice oxygen escape. 100,107,108…”
Section: Challenges Of Low Cobalt Ncm Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…105,106 Cation doping and interface engineering are two of the efficient strategies to prevent the lattice oxygen escape. 100,107,108…”
Section: Challenges Of Low Cobalt Ncm Materialsmentioning
confidence: 99%
“…It is observed that at a highly delithiated stage (voltage > 4.4 V), O 2− oxidation is more favored compared to transition metal oxidation. 99,100 At this stage, the highly reactive Ni 4+ of the Ni-rich NCM moiety reduces to Ni 2+ by oxidizing the electrolyte. In order to maintain the charge neutrality, the lattice O 2− oxidizes and escapes from the NCM lattice.…”
Section: Lattice Oxygen Escape and Phase Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 These unique properties have aroused tremendous research interest in the mechanism investigation and development of Ni-rich cathodes which are highly sensitive to morphology and size distribution. 32,33 Ryu et al 34 found that a traditional single-crystal NCM cathode shows only 91.1% capacity retention aer 100 cycles due to the stress generated by multi-phase coexistence and the uneven Li + concentration inside the single-crystal NCM cathode. Xiao et al 35 observed a reversible planar gliding and microcracking in single crystal NCM in which the stability is governed by reduced crystal size smaller than 3.5 mm and the depth of charge.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4,5 ] For example, the nickel (Ni) in NCM materials is easy to dissolute into electrolyte and deposit on the graphite cathode, while cobalt content will be reduced, resulting in an unstable architecture of the NCM materials, which can easily react with electrolyte to reduce the capacity of LIBs. [ 6,7 ] Therefore, the electrolyte always needs additives to form a dense and homogeneous film that can isolate the electrolyte from the cathode material and prevent the influence of side reactions. [ 8,9 ] Lithium bis(oxalate)borate (LiBOB) is such a classic additive, used to improve the multiplicity and cycling performance of LIBs.…”
Section: Introductionmentioning
confidence: 99%